Found in Alberta Environmental Themes for the Anthropocene. (Environmental humanities., 2014)
Found in Alberta: Environmental Themes for the Anthropocene is a collection of essays about the natural environment in a province rich in natural resources and aggressive in development goals. This is a casebook on Alberta from which emerges a far wider set of implications for North America and for the biosphere in general. The writers come from an array of disciplinary backgrounds within the environmental humanities. The essays examine the oil/tar sands, climate change, provincial government policy, food production, industry practices, legal frameworks, wilderness spaces, hunting, Indigenous perspectives, and nuclear power. Contributions from an ecocritical perspective provide insight into environmentally themed poetry, photography, and biography. Since the actions of Alberta's industries and government are currently at the heart of a global environmental debate, this collection is valuable to those wishing to understand the natural and commercial forces in play. The editors present an introductory argument that frames these interests inside a call for a rethinking of our assumptions about the natural world and our place within it.